Parameters controlling octadecyl phosphonic acid self-assembled monolayers on titanium dioxide for anti-fouling biomedical applications - Thomas Wilkinson (Applied Surface Science, 2022)
Octadecylphosphonic acid (ODPA) self-assembled monolayers (SAMs) have demonstrated potential for deterring bacterial attachment to titanium, however the coating process is time consuming and uses toxic solvents. In this study, ODPA SAM quantity, quality, and structure were evaluated on titanium quartz crystal microbalance (QCM) sensors by varying solvent type (anisole or cyclopentyl methyl ether (CPME), environmentally friendly non-polar solvents); ODPA concentration (0.5 mM or 1 mM); and temperature (21 °C or 60 °C). Surfaces were characterised using QCM frequency and dissipation measurements and Sauerbrey mass calculations; X-ray photoelectron spectroscopy; water contact angle measurements; and temperature-programmed desorption mass spectrometry (TPD-MS). Anti-fouling ability was established against Staphylococcus aureus. Incubation in 0.5 mM ODPA in CPME at 21 °C rapidly formed uniform rigid ODPA SAMs as demonstrated by high Sauerbrey mass (≈285-290 ng/cm2), viscoelastic modelling, high atomic percentage surface phosphorus (1.1 %) and high water contact angles (117.6 ± 2.5°), consistent across the entire sample surface. High temperatures or the use of anisole resulted in suspected multilayer formation, which reduced bacterial attachment. TPD-MS confirmed covalent bonding of ODPA SAMs on TiO2 at ≈ 110–120 °C and thermal stability below 300 °C. This study demonstrates the key parameters that control ODPA SAM formation on titanium and their future potential for biomedical applications.